Uvedba metode pozitivnega matematičnega programiranja v sektorsko modeliranje slovenskega kmetijstva - Kožar, Maja (Acta agriculturae Slovenica, 2011)
The paper presents the key results of the doctoral dissertation by Kožar (2010), which introduced the method of positive mathematical programming (PMP) in sector modelling of Slovenian agriculture in order to enrich the set of empirical tools for quantitative impact analysis of economic and political changes on Slovenian agriculture. CAPRI modelling system, a comparative static partial equilibrium model of European agriculture was applied. The model enables impact assessment of different policz and economic scenarios at the aggregate level of EU27, at the level of Member States groups, Member States or NUTS 2 regions and by individual products. The second goal of the dissertation was to test the introduced approach by comprehensive regional analysis of production and economic impacts of implementing two scenarios of long-term reforms of CAP pillar I direct pazments policy on Slovenian and European agriculture. Model results show that the abolition of direct pazments would result in drop of the baseline income by 17 % at the aggregate EU27 level. The impacts can be less favourable for individual Member States groups, Member States and regions, depending on the share of premiums in income from agriculture, specialization and competitiveness of production. Themost pronounced and the least favourable production impacts are projected for suckler cows. At the level of EU27 suckler cow herd size will drop by 6 % in case of both scenarios compared to the baseline. The most influential is the drop of the herd size in Spain and France as it influences EU27 average and causes the whole chain of impacts for other products. Slovenia is among those, which will be faced with less favourable impacts. The model results could be underestimated due to the fixed land market and due to the nature of modelling production decoupled payments.
Keywords: agriculture; kmetijstvo; kmetijska politika; sektorsko modeliranje; matematično programiranje; Slovenia; Slovenija